Death of an ice cream scooper - Hollis, Lee (Hollis, Lee. Hayley Powell food and cocktails mystery, 2022)
"Food and cocktails columnist Hayley Powell doesn't know what to believe when Lydia Partridge, the put-together owner of gourmet Bar Harbor Ice Cream, suddenly reveals fears that her husband may be having an affair. There's no other way to explain why Jamie, a respected professor, was spotted in a remote part of town with a much younger woman. But instead of learning the truth about the secret meeting, Lydia opens her freezer truck to find another surprise -- the dead body of a summer employee ... The shock continues as photographic evidence proves Jamie was spending time off campus with the victim, one of his students. Now, Lydia desperately needs Hayley to discover if Jamie really is a cheater -- and, worse, a ruthless killer. With her own complicated family issues to address, can Hayley make sense of a popular college girl's love life and out the true culprit before the case, or another person, goes cold?"--